Johan Adam Möhler and N.F.S. Grundtvig: The Bridge of Romanticism - Franklin, R. William (Grundtvig-Studier, 1996)
Johan Adam M.hler and N.F.S. Grundtvig: The Bridge of Romanticism Af R. William Franklin The article has been quoted in Danish in Jakob Balling’s article, page 15If.